PERBEDAAN PENGARUH ENDORSER PADA PERSEPSI RISIKO KONSUMEN - Euis Soliha (Jurnal Bisnis dan Ekonomi, 2007)
This paper examines the differential effects of celebrity and expert endorsements on consumer risk perceptions. There are two hypothesis: (1) Consumers perceived risk will be lower when an expert endorsements rather than a celebrity endorsements in college advertising. (2) Consumers perceived risk will be lower when an expert endorsements rather than a celebrity endorsements in college advertising and this effect will be further magnified for consumer product knowledge. The participant of this research is 102 student (three group:group 1 with the expert endorser advertising, group 2 with the celebrity endorser advertising, and group 3 with the non expert non celebrity endorser advertising). The result of the research are the first hypothesis is supported and the second hypothesis isn’t supported.   Keywords:  endorser,  financial risk,  performance risk